Impact of MG2+ and tara gum concentrations on flow and textural properties of WPI solutions and cold-set gels - M. Vázquez da Silva (2010)
Cold-set gels of whey protein isolate (WPI) and of WPI plus tara gum (TG) were produced through the addition of magnesium chloride to heat-denatured (HD) WPI and WPI+TG solutions. The flow behaviour of the WPI, TG, and WPI+TG samples was analyzed: WPI solutions exhibit Newtonian behavior while the behavior of the TG and WPI+TG solutions can be described through the Cross and Carreau models. The mechanical characterization of the cold-set gels was done through puncture tests, and the Youngs modulus for each coldset gel was obtained. Statistical analysis of the mechanical data was made according to the Marquadt-Levenberg algorithm.